Consumer Protection in Online Virtual Game Object Sales Transactions on Social Media X - Putri Aininda; Muh. Ali Masnun (NOVUM : JURNAL HUKUM, 2025)
Online transactions conducted without face-to-face interaction offer efficiency in terms of distance and time, but on the other hand, because they are not conducted face-to-face, there is a possibility of discrepancies in the items being sold, whether in terms of quantity, form, or quality. Online transactions involving virtual game items conducted through social media platform X also have the potential to encounter the same issues, which would be detrimental to online gamers as consumers. This study aims to analyze consumer legal protection in online game virtual item transactions on social media platform X, as well as the legal measures consumers can take regarding losses incurred in such transactions. This study employs a normative research approach using both a statutory approach and a conceptual approach. The findings reveal that consumer protection in transactions involving the buying and selling of virtual game items is not yet optimal, necessitating legal measures, including through court proceedings and alternative dispute resolution mechanisms via the Consumer Dispute Resolution Agency (BPSK).